Hepatic Steatosis is Common in Adolescents with Obesity and PCOS and Relates to De Novo Lipogenesis but not Insulin Resistance. Issue 11 (November 2016) - Cree‐Green, Melanie; Bergman, Bryan C.; Coe, Gregory V.; Newnes, Lindsey; Baumgartner, Amy D.; Bacon, Samantha; Sherzinger, Ann; Pyle, Laura; Nadeau, Kristen J.
Abstract : Objective: Increased liver fat and type 2 diabetes are prevalent in women with polycystic ovarian syndrome (PCOS) and cause excess mortality, yet little is known about their development during adolescence. The objective of this study was to measure hepatic steatosis and related metabolic contributors in girls with obesity, with and without PCOS. Methods: Nondiabetic adolescents with obesity, 41 with PCOS (PCOS; age 15.0 [13.0‐16.0] years, BMI 35.2 ± 0.61 kg/m 2 ) and 30 without PCOS (OB; age 14.5 [13.0‐17.0], BMI 33.2 ± 1.8), were studied. Visceral and liver fat were assessed with MRI. Serum measures included androgens and 16:1 and 18:1 N7 fatty acids specific to de novo lipogenesis. Adipose, hepatic, and peripheral insulin sensitivity (IS) were assessed with a four‐phase hyperinsulinemic‐euglycemic clamp with isotope tracers. Results: Forty‐nine percent of the PCOS group had hepatic steatosis versus fourteen percent of the OB group ( P = 0.02), and the PCOS group had higher N7 (43 ± 4 vs. 29 ± 5 nmol/g; P = 0.02). Peripheral IS was lower in PCOS (9.4 [7.2‐12.3] vs. 14.5 [13.1‐18.05 mg/lean kg/min]; P < 0.001) as was hepatic ( P = 0.006) and adipose IS ( P = 0.005). Percent liver fat correlated with N7 ( R = 0.46, P = 0.02) and visceral fat ( R = 0.42, P < 0.001), not androgens or peripheral IS. Conclusions: Nearly 50% of nondiabetic girls with PCOS and obesity have hepatic steatosis, which relates to visceral fat and lipogenesis, but not to IS or androgens.